Шоколад - Харрис Джоанн (Культовая классика, 2016)
Экземпляры: Югдонская библиотека (20180125) / Инвентарный номер: 204443 / Цена: 152.87 / Сис.шифр: 84(4Вел) / Авт.знак: Х 21 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)